n-Alkane Characteristics of Thawed Permafrost Deposits Below a Thermokarst Lake on Bykovsky Peninsula, Northeastern Siberia - Jongejans, Loeka L.; Mangelsdorf, Kai; Schirrmeister, Lutz; Grigoriev, Mikhail N.; Maksimov, Georgii M.; Biskaborn, Boris K.; Grosse, Guido; Strauss, Jens (Frontiers in Environmental Science, 2020)
Rapid permafrost thaw by thermokarst mobilizes previously frozen organic matter (OM) down to tens of meters deep within decades to centuries, leading to microbial degradation and greenhouse gas release. Late Pleistocene ice-rich Yedoma deposits that thaw underneath thermokarst lakes and refreeze after lake drainage are called taberal sediments. Although widespread, these have not been the subject of many studies. To study OM characteristics and degradability in thawed Yedoma, we obtained a 31.5 m long core from beneath a thermokarst lake on the Bykovsky Peninsula, northeastern Siberia. We reported radiocarbon ages, biogeochemical parameters (organic carbon (OC) content and bulk carbon isotopes) and n-alkane distributions. We found the most degraded OM in frozen, fluvial sediments at the bottom of the core, as indicated by the lowest n-alkane odd-over-even predominance (OEP; 2.2). Above this, the thawed Yedoma sediments had an n-alkane distribution typical of emergent vegetation, suggesting a landscape dominated by low-centered polygons. These sediments were OC poor (OC content: 0.8 wt%, 60% of samples <0.1 wt%), but the OM (OEP~5.0) was better preserved than in the fluvial sediments. The upper part of the Yedoma reflected a transition to a drier, grass dominated environment. Furthermore, this unit’s OM was least degraded (OEP~9.4). The thermokarst lake that formed about 8 cal ka BP thawed the Yedoma in the talik and deposited Holocene lake sediments containing well-preserved OM (OEP~8.4) with the highest n-alkane concentrations (20.8 μg g-1 sediment). Old, allochthonous OM was found in the thawed Yedoma and frozen fluvial deposits. Using an n-alkane endmember model, we identified a mixed OM input in all units. In our study, the thawed Yedoma sediments contained less OC than reported in other studies for still frozen Yedoma. The Yedoma OM was more degraded compared to previous biomarker research on frozen Yedoma. However, this signal is overprinted by the input signal. The fluvial deposits below the Yedoma contained more OM, but this OM was more degraded, which can be explained by the OM input signal. Continued talik deepening and expansion of this thermokarst lake and others similar to it will expose OM with heterogeneous properties to microbial degradation.